Soybean, cowpea, groundnut, and pigeonpea response to soils, rainfall, and cropping season in the forest margins of Cameroon - Wendt, J.; Atemkeng, M. (Springer, 2004)
Yields of groundnut, the traditional grain legume grown in central and southern Cameroon and in much of the humid zone of Central Africa, are generally low. Other food legumes may provide alternatives to groundnut. On-farm experiments examined the relative yields of up to 15 pigeonpea, 10 groundnut, 7 soybean, and 4 cowpea varieties over three growing seasons in four to six rural communities. Soil analytical values and rainfall data from all seasons were used as covariates in the analysis of variance. In the first two trials, variety-within-species interactions were significant (P < 0.0001 and 0.04). Groundnut var. JL-24 yielded 60% more than local groundnuts in the first season of 2000, while soybean var. TGx1838-5E, local cowpea var. `Mefak' and pigeonpea var. ICEAP 00436 outyielded several other varieties of their respective species. Comparing these selected varieties over three seasons, significant species × community and species × season effects (P < 0.0001) were observed. Covariate analysis showed that soybean yields increased with increasing soil Mg saturation and P levels. Groundnut yielded more in the first season of 2000 compared to the second seasons of 1999 and 2000 (average yields of 927 kg ha−1 vs. 422 and 522 kg ha−1, respectively). Improved yields were related to soil exchangeable Ca levels greater than 5 cmol(+) kg−1 in both second seasons, but not during the first season. Cowpea yields were superior in both second seasons. Pigeonpea yields were unrelated to soil factors, showing its wide adaptability to soil conditions. Pigeonpea, which matured in February during the dry season, was severely affected by the early cessation of rains in 2000. In 1999 yields averaged 820 kg ha−1 across communities. The results show that good food legume alternatives to groundnut exist, particularly for second season production. Species can be targeted to communities based on soil properties and season of production.